UNVEILING IRELAND'S ECONOMIC GROWTH BLUEPRINT: DOES THE CELTIC TIGER MODEL STILL INSPIRE US? - Lakhchini Wassima; Wahabi Rachid; Benghazala Zakaria (Antis Publisher, 2024)
In the past few generations, the examination of the intricate relationship between economic growth and tourism development has been of paramount importance for emerging nations. Within Western Europe, Ireland's extraordinary ascent has emerged as a valuable lesson for other emerging and belatedly developing countries, regions, and even major cities. The compelling narrative of the 'Celtic Tiger' from the mid-1980s to the late 2000s has garnered significant interest from scholars and policymakers intrigued by the economic development model. However, to date, no study has utilized Ireland's economic boom as a case study for another emerging nation or region. This research gap has sparked our curiosity: Can the Celtic Tiger model still offer inspiration in 2024? As a result, our paper's principal objective is to integrate Ireland's economic growth model, specifically between 1985 and 1999, with the imminent government investments in the Dakhla Oued Eddahab region in Morocco. In our research, we will examine the ‘Celtic Tiger’ as a case study, underlying the strengths and weaknesses behind its boom and dust. In addition, we will compare Ireland’s attractiveness during the Celtic Tiger era versus Dakhla Oued Eddahab, in the present and future, along with inferring successful management strategies. Our study results are presented in three future policy suggestions, that may help an emerging country avoid the Celtic Tiger collapse risks. In conclusion, we will propose avenues for future research that can contribute to enhancing sustainable Moroccan investments in Dakhla Oued Eddahab, aligning with the principles of long-term environmental, social, and economic sustainability.